Learners Willingness to Communicate in a Foreign Language: The Role of Informal Digital Learning of English - Arif Nugroho (ELE Reviews: English Language Education Reviews, 2021)
The trend of online teaching and learning in the age of the COVID-19 pandemic has driven contemporary students to learn English in an informal context outside the classroom. Drawing on this issue, the present study is at the cutting edge of examining the role of Informal Digital Learning of English (IDLE) in affecting students willingness to communicate in a foreign language. A total of 156 (male=63; female=93) Indonesian EFL students participated in survey research upon invitation.  The data are obtained by means of an online questionnaire consisting of three parts: (1) willingness to communicate, (2) IDLE, and (3) demographic data. The hierarchical regression analysis results reveal that Frequency of IDLE, Receptive IDLE activity, and Productive IDLE activity are the positive predictors of EFL learners willingness to communicate in English as a foreign language. The results indicate that the Indonesian EFL learners are motivated to communicate in English when engaging in a range of IDLE activities. In other words, it is implied that IDLE activities (both productive and receptive) potentially build the communication behavior of Indonesian EFL learners, who learn English as a foreign language and possess a culturally homogeneous society.